Research progress and prospects of urban resilience in the perspective of climate change - Wang, Wenjing; Wei, Hongbin; Hassan, Hasmadi; He, Xiangyu (Frontiers in Earth Science, 2024)
The natural hazards caused by climate change have a significant impact on the production and life of urban residents, enhancing urban resilience is an important way to cope with climate disasters and ensure the safety of urban systems. Based on the "urban resilience" research relevant literature, the paper applies bibliometric analysis software to reveal the research hotspots and evolution trends of urban resilience in the perspective of climate change. The results indicate that the main research contents can be summarized into four aspects: (ⅰ) influencing factors of urban resilience; (ii) evaluation index and method of urban resilience; (iii) the impact of climate change on urban resilience; (ⅳ) Enhancing urban resilience in response to climate change. Finally, potential directions for future research on urban resilience were proposed, multi-dimensional research on urban resilience should be carried out from aspects of theoretical development, urban planning based on resilience mechanisms should be carried out from the perspective of planning practice, and innovation and reform should be carried out in policy implementation and urban management. Accurately understanding the conceptual connotation and construction mechanism of urban resilience is a crucial premise for climate mitigation and adaptation. Relevant research conclusions can provide useful reference for theoretical research and spatial planning of resilient cities.